Trichoderma Biology and Applications - Mukherjee, Prasun K (CABI, 2014)
After decades of improvement of agriculture and chemical production towards industrialized processes, environmental issues and sustainability needs initiated movement for a greener industry and agriculture. Several principles are needed to make agriculture sustainable. One of these is to use natural biological control, where possible. The idea to use members of the genus Trichoderma to control plant pathogens can be traced back to before the middle of the last century, but the past decade has seen a qualitative leap in the tools and approaches for under- standing these beneficial fungi and their interaction with plants. In addition, however, the industrial production of chemicals and enzymes has started to shift towards biotechnological processes, in many cases applying filamentous fungi as work horses. Here also, Trichoderma is a major organism, especially with the research focus on second-generation biofuels. The landmark achievement since the last monograph on Trichoderma is, without doubt, the publication of the genomes of three species. Other paradigm shifts are almost as important. One is the realization that induction of resistance in the plant rivals direct killing of pathogenic fungi as a mechanism for control of disease. Another is the ability to do genetic crosses in Trichoderma species that were thought to lack a sexual cycle under laboratory-defined conditions. Methods for engineer- ing of strains have been optimized. Next-generation sequencing is becoming the best way to follow gene expression, as well as to identify the genes corresponding to classical mutant phenotypes. The concept of this book grew, in part, from our participation in the genome projects. Sequencing shone a spotlight on the genus Trichoderma, the most important members of which, from the biotech- nological point of view, are often hidden underground in the rhizosphere or within plants as endo- phtyes. We were further encouraged by our dialogue with an international community of researchers who focus in every aspect from molecular genetics to field applications. The chapters in this volume address basic biology, morphogenesis in response to light and other signals, genetics, interactions with plants and secondary metabolites, just to mention a few of the topics. The collection of diverse approaches should serve as a link between genomes and biology. Moreover, we trust that having this information, critically reviewed and within easy reach, will encourage the connections that start new research. Finally, we hope that the unfolding of the story of Trichoderma research will provide an enjoyable path through the myriad of biotechnological and genetic details.